Cash operating income and liquidity management for swine farms - B D Elliott; Michael R Langemeier; Allen M Featherstone (Kansas Agricultural Experiment Station Research Reports, 1994)
Net cash flow measures the amount of cash remaining after all cash expense obligations are satisfied. This cash is available for additional farm investment, off-farm investment, family living, and additional debt repayment. A 5-year average monthly cash flow statement was used to determine net cash flow for 13 swine farms. Results indicate that excess cash was used primarily to invest in machinery, vehicles, and nonfarm assets and to increase the allocation for family living. Investments in buildings increased moderately over the study period, but investment in land was minimal. Investment in additional swine facilities was small. Expansion of the breeding herd was not visible on these farms until 1992.; Swine Day, Manhattan, KS, November 17, 1994
Keywords: Swine day; 1994; Kansas Agricultural Experiment Station contribution; no. 95-175-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 717; Swine; Cash flow; Liquidity; Investment